THE EFFECTIVENESS OF CHARACTER EDUCATION IN IMPROVING STUDENT DISCIPLINE IN ELEMENTARY SCHOOLS - Loso Judijanto; Moh. Miftahul Arifin; Kadek Dedy Herawan (Indonesian Journal of Education (INJOE), 2025)
This study aims to examine the effectiveness of character education in improving student discipline in elementary schools through a literature review approach. Character education is an important aspect in the world of education, especially in forming disciplined behavior from an early age. This study analyzes various sources such as journal articles, theses, and books that are relevant and published in the last ten years. The results of the study indicate that the implementation of character education integrated into subjects, extracurricular activities, and school culture has a positive impact on improving student discipline. Supporting factors such as principal leadership, teacher and parent involvement, and adequate facilities also strengthen the success of this program. On the other hand, limited teacher training and inconsistent application of values are major obstacles. This study concludes that character education that is implemented in a planned, consistent, and collaborative manner has proven effective in forming disciplined behavior in elementary school students.